Proposing Utilization of Photovoltaic (PV) Source into Power Distribution Network Using University of Port Harcourt as a Case Study - Omorogiuwa Eseosa; Noel Iloayira Wariboko (Journal of Robotics and Control (JRC), 2021)
Relying on Power Holding Company of Nigeria (PHCN) for power distribution in University of Port Harcourt (Uniport) has not really helped in satisfying the overall power requirements, considering the fact that alternative renewable sources of power exist in its environs and tapping into it will help ameliorate these challenges. This work involves proposing utilization of photovoltaic (PV) source into power distribution using Uniport as a case study. Solar radiation profile was obtained as latitude 40o48.1 oN and longitude 6o55.9oE with average clearance index of 4.37kwh/m2/day. Solar altitude, angle of incidence, azimuth, global solar value in kw/m2 were recorded as well as models for PV, battery bank and converter components formulated. Moreso, sensitivity and optimization studies including systems architecture, load and PV output for the solar network was carried out. User specified variables such as appliance peak power, total energy produced/consumed per day, total amount to be invested as well as lifespan of solar generating plant. Overall cost of solar PV amounted to about Two billion, seven hundred and forty million, six hundred thousand naira (N2, 740,600,000) for a twenty-four (24) hour power supply. Operation and maintenance cost for a projection of twenty-five (25) years (OPEX was also determined to be Ninety-six million, five hundred thousand naira (N96, 500,000:00). At 25 years, amount that must have been spent on bills to PHEDC for consuming maximum of ten (10) hours of electrical power is about Seven billion, eight hundred and sixteen million, three hundred and thirty-one thousand, one hundred naira (N 7,816,331,100:00). This implies that if Uniport decides to jettison PHEDC for the next twenty-five (25) years and want to be sure of a guaranteed 24 hours’ power supply, it would have saved a total of Five billion, and seventy-five million, seven hundred and thirty-one thousand, one hundred naira (N5,075,731,100:00). Furthermore, generated power by this design is 7500MWhr but the load consumed in a year is 7100MWhr/year given an excess used power of 400MWhr/year. This excess power can be sold thereby creating extra profit for the institution.